2014
DOI: 10.1016/j.ijhydene.2014.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Performance stability and degradation mechanism of La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3−δ cathodes under solid oxide fuel cells operation conditions

Abstract: Performance stability and degradation mechanism of La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ cathodes under solid oxide fuel cells operation conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 31 publications
(33 reference statements)
4
38
0
Order By: Relevance
“…For example, deactivation in LSCF cathodes has frequently been associated with segregation of Sr cations. [27][28][29] The high degree of compositional control provided by ALD of Fe 2 O 3 may allow titration of the Sr in the form of SrFeO 3 and re-activation of the electrode. 30,31 Finally, we suggest that ALD has great promise for producing electrodes with complex and potentially promising surface structures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, deactivation in LSCF cathodes has frequently been associated with segregation of Sr cations. [27][28][29] The high degree of compositional control provided by ALD of Fe 2 O 3 may allow titration of the Sr in the form of SrFeO 3 and re-activation of the electrode. 30,31 Finally, we suggest that ALD has great promise for producing electrodes with complex and potentially promising surface structures.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, less effective reaction areas and more secondary insulating phase formation suppress the overall oxygen reduction reaction activity. It has been found that partial decomposition of the perovskite usually has severely influence on the cell degradation than interface reactions during the operation [ [116][117][118][119][120][121][122][123].The improvement of cathode long-term performance is one of the most important issues for the development of IT-SOFCs.…”
Section: Electrolytementioning
confidence: 99%
“…However, the Sr contained in SBSCO causes segregation on the surface, causing problems such as reduction of electrochemical properties and long-term performance (Liu et al, 2014;Zhao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%